2015
DOI: 10.1007/s40368-015-0207-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for anterior traumatic dental injury in children and adolescents with autism spectrum disorders: a case–control study

Abstract: Children and adolescents with ASD exhibit different risk factors for TDI compared with those without ASD, and girls with ASD are more prone than boys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
46
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 28 publications
4
46
0
2
Order By: Relevance
“…to surrounding obstacles, 7,[9][10][11] hyperactivity as in ADHD, 6,8 lack of coordination and sensation of the surroundings (visual and hearing impairment), 17,18 or changes in behavior and social interaction (ASD). 4 The current study found a comparable prevalence of TDI among different medical conditions similar to those in previous studies (6.2-20%). 15,16 Correlations between TDI and the medical condition showed that there was a statistically significant relationship between TDI and intellectual disabilities as well as visual and hearing impairments.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…to surrounding obstacles, 7,[9][10][11] hyperactivity as in ADHD, 6,8 lack of coordination and sensation of the surroundings (visual and hearing impairment), 17,18 or changes in behavior and social interaction (ASD). 4 The current study found a comparable prevalence of TDI among different medical conditions similar to those in previous studies (6.2-20%). 15,16 Correlations between TDI and the medical condition showed that there was a statistically significant relationship between TDI and intellectual disabilities as well as visual and hearing impairments.…”
Section: Resultssupporting
confidence: 91%
“…2 These individuals are at higher risk for traumatic dental injuries (TDI), which may be related to the nature of the medical condition and factors such as neurological, intellectual, behavioral, and physical impairments. [4][5][6] Previous studies of TDI in CSHCN have concentrated on individual types of medical diagnosis, such as cerebral palsy, autism, and attention deficit hyperactivity disorder (ADHD), with regard to the prevalence of TDI, types, causes, or seeking treatment behavior in children. [4][5][6] Previous studies of TDI in CSHCN have concentrated on individual types of medical diagnosis, such as cerebral palsy, autism, and attention deficit hyperactivity disorder (ADHD), with regard to the prevalence of TDI, types, causes, or seeking treatment behavior in children.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The studies were evaluated for quality assessment of different topics and their methodological quality was defined through the answers to three summary questions. Of the 28 articles, only three studies had “YES” answers for all summary questions, thus being classified as high methodological quality. The others studies showed methodological problems (Table ).…”
Section: Resultsmentioning
confidence: 99%